Shared decision-making following anterior cruciate ligament rupture: a mixed methods feasibility study - Carter, Hayley (2025)
BACKGROUND Anterior cruciate ligament (ACL) ruptures are common, affecting over 20,000 people in the UK each year. Treatment may follow a surgical, non-surgical (rehabilitation) or combined pathway whereby patients engage with rehabilitation prior to surgical intervention. Most commonly, surgery is the treatment of choice. Not all patients receive rehabilitation prior to surgery, this may be due to a lack of evidence supporting its efficacy on improving post-operative treatment outcomes. Previous research has also identified that rehabilitation prior to surgery varies. However, all patients in the UK will routinely have rehabilitation after surgery.